Racism in New Zealand - Haenga-Collins, M; Tudor, K (Egalitarian Publishing Ltd, 2021)
This article presents how racism is manifested in Aotearoa New Zealand, targets and disadvantages Maori as tangata whenua (the first people of this land), and cannot be understood without reference to colonisation.
Keywords: Marginalization; Pākekā; Colonization